Suberanilohydroxamic acid prevents TGF-β1-induced COX-2 repression in human lung fibroblasts post-transcriptionally by TIA-1 downregulation - Pasini, Alice; Brand, Oliver J.; Jenkins, Gisli; Knox, Alan J.; Pang, Linhua (Elsevier, 2018)
Cyclooxygenase-2 (COX-2), with its main antifibrotic metabolite PGE, is regarded as an antifibrotic gene. Repressed COX-2 expression and deficient PGE have been shown to contribute to the activation of lung fibroblasts and excessive deposition of collagen in pulmonary fibrosis. We have previously demonstrated that COX-2 expression in lung fibroblasts from patients with idiopathic pulmonary fibrosis (IPF) is epigenetically silenced and can be restored by epigenetic inhibitors. This study aimed to investigate whether COX-2 downregulation induced by the profibrotic cytokine transforming growth factor-β1 (TGF-β1) in normal lung fibroblasts could be prevented by epigenetic inhibitors. We found that COX-2 protein expression and PGE production were markedly reduced by TGF-β1 and this was prevented by the pan-histone deacetylase inhibitor suberanilohydroxamic acid (SAHA) and to a lesser extent by the DNA demethylating agent Decitabine (DAC), but not by the G9a histone methyltransferase (HMT) inhibitor BIX01294 or the EZH2 HMT inhibitor 3-deazaneplanocin A (DZNep). However, chromatin immunoprecipitation assay revealed that the effect of SAHA was unlikely mediated by histone modifications. Instead 3'-untranslated region (3'-UTR) luciferase reporter assay indicated the involvement of post-transcriptional mechanisms. This was supported by the downregulation by SAHA of the 3'-UTR mRNA binding protein TIA-1 (T-cell intracellular antigen-1), a negative regulator of COX-2 translation. Furthermore, TIA-1 knockdown by siRNA mimicked the effect of SAHA on COX-2 expression. These findings suggest SAHA can prevent TGF-β1-induced COX-2 repression in lung fibroblasts post-transcriptionally through a novel TIA-1-dependent mechanism and provide new insights into the mechanisms underlying its potential antifibrotic activity.